Research agenda on the evolution of digital transformation in the textile sector: a bibliometric analysis and research trends - María Camila Bermeo-Giraldo; Alejandro Valencia-Arias; Ezequiel Martínez Rojas; Sebastián Cardona-Acevedo; Paula Andrea Rodríguez-Correa; Juan David González-Ruiz; Wilmer Londoño-Celis; Raúl Bao García (Discover Sustainability)
Abstract Digital transformation has been identified as a primary catalyst for sustainability and competitiveness in the textile industry. The implementation of strategic and efficient solutions, including automation of tasks, virtual reality, and big data, is driving these advancements. However, extant literature on the subject reveals significant gaps regarding the impact of digital transformation on business performance within the sector. The objective of this study is to examine research trends related to digital transformation in the textile sector, with a particular focus on how these technologies enhance company performance in terms of productivity, product quality, and customer satisfaction. A bibliometric analysis is conducted using the Web of Science and Scopus databases, following PRISMA guidelines. The analysis identifies the United States and the United Kingdom as leaders in this research area, and highlights sustainability and supply chain management as growing topics in academic literature. The study further identifies significant themes for the future research agenda, including the use of artificial intelligence in supply chain management, e-commerce in sales management, and the need to develop digital skills and ethical considerations for professionals in the sector. The findings demonstrate that the implementation of digital technologies and platforms has enhanced product quality and customer satisfaction, while facilitating market expansion. From a policy perspective, it is recommended that governments support innovation, digital skills development, and collaboration among stakeholders to foster sustainable growth in the textile sector.